2021
DOI: 10.3390/min11030270
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic Variations of Fe–Mn Micronodules and Implications for the Formation of Extremely REY-Rich Mud in the Western North Pacific Ocean

Abstract: The origin of deep-sea sediments in the western North Pacific Ocean, which are significantly enriched in rare-earth elements and yttrium (REY), and its paleoceanographic implications have been poorly constrained. Here, we investigated stratigraphic variations in the chemical compositions and textures of ferromanganese (Fe–Mn) micronodules separated from western North Pacific sediments. The characteristics of the micronodules of an extremely REY-rich mud layer vary from almost purely diagenetic to relatively hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Previous research applied radiogenic isotopes to the sediments in the western North Pacific, where the sediments similar to those in deep‐sea basins around Minamitorishima exist, to discuss binary mixing between Chinese Loess and volcanic ash (Asahara, 1999; Asahara et al., 1999; Jones et al., 1994, 2000; Nakai et al., 1993). However, pelagic clay in the area around Minamitorishima Island also contains biogenic calcium phosphate (BCP) and hydrogenous Mn‐oxides (Takaya et al., 2018; Yasukawa et al., 2020, 2021). Thus, for a comprehensive understanding of the depositional history of pelagic clay, various components should be discussed, which will place the pelagic clay research in a broader context than before.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research applied radiogenic isotopes to the sediments in the western North Pacific, where the sediments similar to those in deep‐sea basins around Minamitorishima exist, to discuss binary mixing between Chinese Loess and volcanic ash (Asahara, 1999; Asahara et al., 1999; Jones et al., 1994, 2000; Nakai et al., 1993). However, pelagic clay in the area around Minamitorishima Island also contains biogenic calcium phosphate (BCP) and hydrogenous Mn‐oxides (Takaya et al., 2018; Yasukawa et al., 2020, 2021). Thus, for a comprehensive understanding of the depositional history of pelagic clay, various components should be discussed, which will place the pelagic clay research in a broader context than before.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, KCA is a conventional method that can classify data into a limited number of groups or clusters following a multivariate data structure (MacQueen, 1967). Notably, Iwamori et al (2017) demonstrated that applying KCA on whitened data (i.e., preprocessed data with uncorrelated variables, zero mean, and unit variance) highlights the essential structure of the data set and provides each sample with objective data labeling that reflects their inherent features (Hamada et al, 2020;Iwamori et al, 2017Iwamori et al, , 2020Yasukawa et al, 2021).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The importance of investigations about other mineral resources related to ferromanganese nodules was highlighted by Yasukawa et al [4], Hong et al [5], and Pérez et al [6]. Yasukawa et al [4] focused on stratigraphic variations in geochemistry, morphology, and surficial textures of micronodules in REY-rich mud.…”
mentioning
confidence: 99%
“…The importance of investigations about other mineral resources related to ferromanganese nodules was highlighted by Yasukawa et al [4], Hong et al [5], and Pérez et al [6]. Yasukawa et al [4] focused on stratigraphic variations in geochemistry, morphology, and surficial textures of micronodules in REY-rich mud. Their results showed that micronodules are an important indicator of the environment of sedimentation in forming REY-rich mud at the seafloor surface and indicate the history of oxygen supply or consumption in response to the dynamics of bottom currents.…”
mentioning
confidence: 99%
See 1 more Smart Citation